Addressing fisheries bycatch in a changing world - Komoroske, Lisa M.; Lewison, Rebecca L. (Frontiers in Marine Science, 2015)
Fisheries bycatch is a threat to species of marine megafauna across the world’s oceans. Work over the past several decades has greatly advanced our understanding of the species affected, the magnitude and the spatial extent of bycatch. In the same time period, there have been substantial advances in the development of mitigation strategies and best practices to reduce bycatch. In this paper, we take stock of bycatch knowledge and science to address the critical question “Where do we go from here?” First, we review the current state of global bycatch science, including bycatch rate estimation and biological effects of bycatch, and bycatch mitigation practices and gear. We then identify knowledge gaps as well as socio-cultural constraints that hamper effective knowledge transfer or implementation, and discuss emerging transdisciplinary approaches to address these issues. Finally, we discuss the need to consider bycatch in a changing ocean and socio-cultural context where species, ecosystems, and people are responding to multiple stressors and dynamic conditions. As the field of bycatch research moves into the 21st century, a new perspective is needed to develop responsive strategies that effectively address the shifting ecological, social, cultural and economic contexts of the global bycatch seascape.